Studying GPCR/cAMP pharmacology from the perspective of cellular structure - Wright, Peter T.; Schobesberger, Sophie; Gorelik, Julia (Frontiers in Pharmacology, 2015)
Signal transduction via G-protein coupled receptors (GPCRs) relies upon the production of cAMP and other signaling cascades. A given receptor and agonist pair, produce multiple effects upon cellular physiology which can be opposite in different cell types. The production of variable cellular effects via the signaling of the same GPCR in different cell types is a result of signal organization in space and time (compartmentation). This organization is usually based upon the physical and chemical properties of the membranes in which the GPCRs reside and the repertoire of downstream effectors and co-factors that are available at that location. In this review we explore mechanisms of GPCR signal compartmentation and broadly review the state-of-the-art methodologies which can be utilized to study them. We provide a clear rationale for a ‘localized’ approach to the study of the pharmacology and physiology of GPCRs and particularly the secondary messenger cAMP.